Digital Library-Based LMS with TRINGO Strategy: Cross-Tradition Approach for Technological Content Knowledge Development - Muhammad Najmi Alwi Sinaga; Muhibuddin Fadhli; Ahmad Alief Al Fawaz; Fikri Aulia (Jambi Tuah Tengganai, 2026)
Indonesian faith-based educators lack structured digital environments that integrate pedagogical strategies with the development of Technological Content Knowledge. This Research and Development study, following the Lee and Owens model, developed and validated a digital library-based Learning Management System operationalizing Ki Hadjar Dewantara's TRINGO strategy (Ngerti, Ngrasa, Nglakoni) as a cross-tradition learning architecture for Muhammadiyah educators. 45 educators from 21 Malang City schools completed a 4-week training cycle. Expert validation across media (95%), content (90%), and learning strategy (100%) domains classified the LMS as Highly Valid. A focus group discussion with 21 school principals revealed an institutional appetite for structured teacher development and a resonance between TRINGO's tripartite structure and Muhammadiyah's Pendidikan Berkemajuan commitments. Class-level Technological Content Knowledge improved by eighteen percentage points from pre-test (42%) to post-test (60%). Critically, post-test performance plateaued below the seventy-percent mastery threshold, with the affective Ngrasa dimension showing the smallest gains, suggesting that four weeks suffice for procedural learning but not for deeper reflective engagement. The study contributes a validated cross-tradition prototype for faith-based teacher development while identifying the boundary conditions of its application. Future research requires multi-site replication, extended training cycles, and deeper integration of Muhammadiyah's own pedagogical sources to address the affective dimension.